THE MODEL OF GROW ME FOR DEVELOPING THE CHILDREN FRIENDLY SCHOOL - Slam, Zaenul (JMIE (Journal of Madrasah Ibtidaiyah Education), 2020)
This study is aimed to know the model of GROW ME for developing the children friendly school.This research was conducted at SMP Negeri 3 Majalengka Majalengka Regency on February 2, 2018 until May 30, 2018. The research method used wasÂ  school action research consisting of two cycles and each cycle consisted of four activities, namely: planning, action, observation and reflection. Data was collected using a sheet of instrument monitoring the evaluation of child friendly school to obtain a picture of the achievement of the development of child friendly schools. Data analysis to obtain a picture of the achievement of the development of chil -friendly schools with a percentage value. Based on the results of quantitative analysis: First, the planning dimension obtained an average cycle of 80% (good category) and cycle 2 of 90% (very good category). Second, the action Â dimension obtained an average of 1 cycle 80.82% (good category) and cycle 2 90% (very good category). This shows that there are significant differences in the increase of child-friendly school in both the planning and action dimensions in Cycle 1 and Cycle 2.